(3eNJUQ eQBI GdReGf dHSW Hf GdLhRis - (3ehSi Hf eMeO Hf CHj GdMSjf CMeO Gdjhfjfj GdHYdHcj, bWH GdOjf, CHh GdaJM , (B726 (3g` s; (3SHW GHf GdLhRj , jhSa Hf bRGhZdj Hf YHO Gddg GdHZOGOj GdOeTbj GdMfaj, TeS GdOjf CHh GdeXaQ ,SHW GHf GdLhRj,J (B654 (3g` s
(3ChdgG (B:s
(3jHOC ef HbjI GdSfI (B65(3g` s
(3BNQgG (B:s
(3hjfJgi CKfGA SfI (B92(3g` s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B138 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs